The Role of the Integration of Accounting Information Systems in Enhancing the Economic Value of Information and its role in Rationalizing Administrative Decisions: An applied study on the Regional Commercial Bank for the Period 2015-2024. - Sendw, Ahmed; Abbood, Abbas; Talib, Ali (Indonesian Journal Publisher, 2025)
The research aims to study the integration of the role of organized accounting information systems to improve the accounting of the economic value of information and enhance the rationalization of administrative decisions, through an applied study in the commercial banking sector for the period (2015-2024). importance Search from The role pivotal that Play it Information Accounting minute and integrated in to support Operations Taking decision Administrative The effective one, and reduce Risks Finance And administrative, and strengthening Efficiency operational For institutions Banking. Approved, Search on Curriculum Descriptive Analytical, with Use tools collection Data represented in questionnaires and interviews In addition to analysis Documents and reports Finance For the bank during a period The study. As well. It was completed Use Methods Statistics To analyze Relations between integration Organized Information Accounting Quality Information Economic Rationalization Decisions Administrative. It showed results Search presence relationship Positive strong between integration Organized Information Accounting and improving Value Economic For information, Which Contributes In a way tangible in to support Decisions Administrative The wise one. As well Showed Results presence relationship Positive strong between level integration Systems Accounting and value Economic For information, Which mirror In turn on to improve practical Rationalization Decisions Administrative, especially in Fields Planning strategic, censorship Finance, and management Risks. And based on that, Recommended Search Necessity Strengthening integration between Organized Information different At the bank, Training employees on Use Technologies Modern, and benefit from Information Accounting Integrated To achieve performance administrative What's wrong with better.